PENDIDIKAN ISLAM MULTIKULTURAL SEBAGAI PARADIGMA BARU PENDIDIKAN ISLAM - Ichsan Isroi; Nur Cholid; Ghufron Hamzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The growing social, cultural, and religious diversity of Indonesian society demands a paradigm of Islamic education that is capable of managing differences in a constructive and ethical manner. Amid increasing identity polarization and the challenges of strengthening religious moderation, Islamic education is required to move beyond a doctrinal–transmissive approach toward a more inclusive and dialogical orientation. This study aims to reconstruct Multicultural Islamic Education as a new paradigm of Islamic education and to address the question of how its core concepts, values, and principles are formulated and what implications they hold for the development of Islamic education in Indonesia. This research employs a qualitative approach with a library research design, in which data are collected through systematic and critical analysis of scholarly books and journal articles indexed in Google Scholar published between 2014 and 2025. Data analysis is conducted using content analysis and thematic analysis to synthesize key concepts, core values, and the theological, sociological, and pedagogical dimensions of multicultural Islamic education. The findings indicate that multicultural Islamic education constitutes an integrative paradigm grounded in the values of justice, compassion, ta‘āruf, tolerance, and dialogue, and serves as a strategic framework for strengthening religious moderation. This paradigm contributes theoretically to the enrichment of Islamic education scholarship and practically to the development of curriculum design, instructional strategies, and institutional culture in Islamic educational settings. The study concludes that multicultural Islamic education is highly relevant for addressing contemporary pluralistic challenges, while further empirical research is recommended to examine its contextual implementation in educational practice